Metformin Exposure in First Trimester of Pregnancy and Risk of All or Specific Congenital Anomalies: Exploratory Case-control Study. Issue 1 (March 2019) - Given, J.E.; Loane, M.; Garne, E.; Addor, M.C.; Bakker, M.; Bertaut-Nativel, B.; Gatt, M.; Klungsoyr, K.; Lelong, N.; Morgan, M.; Neville, A.J.; Pierini, A.; et al.
Abstract : ( BMJ . 2018;361:k2477) Metformin is a commonly used drug for the treatment of type 2 diabetes. It has also been used in women with polycystic ovary syndrome to improve insulin sensitivity. Since 2008 the drug has been recommended for use in pregnancy in the United Kingdom for women with type 2 diabetes or gestational diabetes. However, its use in pregnancy remains controversial as it affects stem cell function and concerns have been raised about potential teratogenic effects. Animal studies and meta-analyses in humans have not provided evidence of increased risk for congenital anomalies. However, one cohort study involving 392 women did report an increased risk of congenital anomalies in women taking metformin for diabetes, but no increased risk was found when the drug was being taken for other indications. This led those investigators to conclude the increased risk of anomalies was related to the patients' diabetes and not the exposure to metformin. In contrast, it has also been suggested that metformin could decrease the risk of congenital anomalies in parturients with diabetes by improving glycemic control. This current study aimed to investigate the effect of first trimester metformin exposure on all or specific congenital anomalies by using a European database.